2002
DOI: 10.1161/01.cir.0000018744.58460.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ezetimibe Coadministered With Atorvastatin or Simvastatin in Patients With Homozygous Familial Hypercholesterolemia

Abstract: Background-Patients with homozygous familial hypercholesterolemia (HoFH) have a high incidence of cardiovascular morbidity and mortality from premature atherosclerosis, and the efficacy of pharmacological therapy has been limited. We evaluated the efficacy, safety, and tolerability of ezetimibe, a novel cholesterol absorption inhibitor, in a multicenter, double-blind, randomized trial of HoFH patients receiving atorvastatin or simvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
208
2
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(236 citation statements)
references
References 33 publications
7
208
2
19
Order By: Relevance
“…3 Even in the developed countries, the data on efficacy and safety of various lipid lowering therapies is limited. 4,5,7 We did not observe statin induced myopathy in our patients although a recent Indian study shows that 7.5% of adult statin users developed myopathy.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…3 Even in the developed countries, the data on efficacy and safety of various lipid lowering therapies is limited. 4,5,7 We did not observe statin induced myopathy in our patients although a recent Indian study shows that 7.5% of adult statin users developed myopathy.…”
Section: Discussioncontrasting
confidence: 69%
“…5 In this context, our experience is similar to studies in patients with HeFH which showed LDL-C reductions of upto 55% with maximally tolerated doses of combinations of statins and ezetimibe. [4][5][6][7] Further reductions in plasma lipid concentrations are possible with LDL apheresis which is widely practiced in developed countries but has only recently been conducted successfully in India. 8 The increase in HDL-C achieved in our patients was more as compared to previous studies (29.7% versus 5-10 %).…”
Section: Discussionmentioning
confidence: 99%
“…Одним из препаратов этого класса является АМG145 (эволукумаб). В двойном слепом исследовании продемонстрировано, что эво-лукумаб эффективно снижает уровень холестерина ЛПНП у пациентов с гетерозиготной гиперхолесте-ринемией в случае, если комбинированная терапия статинами и эзетролом не позволяет достичь целевого уровня холестерина [28]. В исследованиях по приме-нению эволукумаба для лечения гомозиготной ги-перхолестеринемии показано, что препарат снижает уровень холестерина ЛПНП только у «рецептор-де-фектных» пациентов [29,30].…”
Section: лечениеunclassified
“…38 The finding that ezetimibe lowers LDL-C levels in subjects with homozygous familial hypercholesterolemia indicates that the rate of production of LDL may fall in response to the reduction in cholesterol absorption. 39 The extent to which the LDL-C-lowering effect of ezetimibe may also reflect upregulation of hepatic LDL receptor activity has not been determined. Ezetimibe blocks the absorption of cholesterol and plant sterols, but does not affect the absorption of bile acids, fatty acids, fat soluble vitamins, or triglycerides.…”
Section: Ezetimibe a Novel Potent And Specific Cholesterol Absorptmentioning
confidence: 99%